Consolidating work from home as the new norms: internal vs external factors among UiTM staff / Salmiwati Othman …[et al.] - Othman, Salmiwati; Ladisma Awis, Mahadir; Abdul Samad, Suhaimi; Harun, Ainul Fadzilah (Universiti Teknologi MARA, 2021)
In recent years, the focus on the challenges regarding work from home (WFH) has been escalating throughout the globe. In the context of Malaysia, seeing that this is an emergent issue, there are still limited studies conducted on the framework or model that promote the effectiveness of WFH. However, there are fundamental issues that need to be addressed, namely; (i) the accessibility and coverage; (ii) the acceptance level among the staff and (iii) the quality of productivity. This study outlines two main objectives, which are (i) to examine the internal factors; and (ii) the external factors that influence the staff while WFH during MCO. Thus, there is an increasing need to recognise the benefits and potential challenges towards assisting the human resource practitioners to be more effective in implementing the WFH (Nordin et al., 2016). This study was conducted among the staff of Universiti Teknologi MARA (UiTM) during the Movement Control Order (MCO) from 18 March till 9 June 2020. Based on the survey conducted among 17,541 staff (as per 31 Mac 2020), 1,320 staff volunteered to be involved in this survey. The data was analysed using the SPSS v26. In part, the analysis was carried out to ascertain the main challenges comprising of internal and external factors. From the internal factor, the findings showed that flexible working hour was found as the main factor; mean value of 4.10. Furthermore, for the external factor, the factor on the distraction due to other commitments such as parent/child caretaker and house chores was found as the main factor; mean value of 3.82. The findings of this study significantly contribute towards understanding the internal and external factors of WFH, and serve to measure the productiveness and the effectiveness of WFH from the viewpoint of higher learning institutions.